Combined hamartoma of the retina and retinal pigment epithelium. (16th November 2012) - Xue, Kanmin; Mellington, Faye; Gout, Irina; Rokerya, Sofia; Olurin, Oyinkan Ibironke; El-Amir, Ahmed
Abstract : We report two cases of combined hamatoma of the retina and retinal pigment epithelium (CHR-RPE), illustrated with ultrasonography, optical coherence tomography, fundus fluorescein angiography and indocyanine green angiography images. CHR-RPE could clinically mimic several other retinal conditions. Failure to distinguish it from serious malignancies such as choroidal melanoma or retinoblastoma has led to unnecessary enucleation in the past. Through these case reports and a review of literature, we show the diagnostic features of CHR-RPE, its key differential diagnoses and the management options.